Financing Greener and Climate-Resilient Infrastructure in Developing Countries--Challenges and Opportunities - Fay, Marianne; Iimi, Atsushi; Perrissin-Fabert, Baptiste (2012)
Climate change complicates this challenge, affecting the way we design and manage infrastructure (defined here as transport, power, water, and sanitation) and increasing costs. But all is not negative: climate change affects both the economic and financial analysis of infrastructure projects in a way that could help achieve long-pursued but elusive goals, such as better maintenance and greener, more efficient design. Furthermore, climate finance could bring additional financing, although that will require increasing the scale of available resources and addressing the fact that climate finance tends to provide ex post financing, ill-suited to a sector characterized by a need for substantial ex ante funding.